Analysis on Problematic Financing - Maria Lusiana Yulianti; Yuliana Yuliana; Dedy Suryadi; Andiena Nindya Putri; Syamsu Rijal (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study explores the funding issue of PT. N usa BPR Cianjur in anticipation of a financial disaster. This study adopts a descriptive qualitative research style and relies on interviews and other primary and secondary data sources. The results of the analysis show that problematic financing at PT. N usa BPR Cianjur includes incorrect or money-shortening financing. Every financial organisation that offers funding aspires to keep problems at bay, but they frequently arise. In order to avoid losses when dealing with problematic financing, a financing settlement strategy must be established. Financing issues can be resolved by rearranging, rescheduling, and upgrading.